2018
DOI: 10.1164/rccm.201706-1066le
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Does Not Predict Exacerbation Rate or Mortality in Chronic Obstructive Pulmonary Disease

Abstract: Cardiovascular disease (CVD) is common in patients with chronic obstructive pulmonary disease (COPD) (1-4), yet it is unclear whether its presence increases the incidence of acute exacerbations (AECOPD) or the risk of death. Observational studies have shown that COPD is associated with a 2-5 times higher risk of ischaemic heart disease (IHD), cardiac dysrhythmia, heart failure, diseases of the pulmonary circulation, and diseases of the arteries, compared with non-COPD populations (4,5). A prospective evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…The primary care-based ACCESS study in European patients with COPD, with and without cardiovascular disease (CVD), reported an acute exacerbation rate of 0.63 per patient per year ( Figure 1B ). 30 This is similar to the exacerbation rate reported for the Japanese cohort in the UPLIFT study (0.61 per patient per year). 7 However, it should again be noted that baseline characteristics of the two study populations were different: patients in ACCESS had a mean age of 66.1 years, mean BMI 27.2 kg/m 2 , 70% were male, 26.6% were GOLD stage III, and 6.3% were GOLD stage IV, 30 while those in the Japanese cohort of UPLIFT had a mean age of 68.0 years, mean BMI 20.7 kg/m 2 , 96% were male, 56% were GOLD stage III, and none were GOLD stage IV.…”
Section: Introductionsupporting
confidence: 86%
“…The primary care-based ACCESS study in European patients with COPD, with and without cardiovascular disease (CVD), reported an acute exacerbation rate of 0.63 per patient per year ( Figure 1B ). 30 This is similar to the exacerbation rate reported for the Japanese cohort in the UPLIFT study (0.61 per patient per year). 7 However, it should again be noted that baseline characteristics of the two study populations were different: patients in ACCESS had a mean age of 66.1 years, mean BMI 27.2 kg/m 2 , 70% were male, 26.6% were GOLD stage III, and 6.3% were GOLD stage IV, 30 while those in the Japanese cohort of UPLIFT had a mean age of 68.0 years, mean BMI 20.7 kg/m 2 , 96% were male, 56% were GOLD stage III, and none were GOLD stage IV.…”
Section: Introductionsupporting
confidence: 86%
“…This is further supported by Cerezo Lajas et al who reported that COPD patients with destabilised HF were at 5.25 times greater odds (95%CI: 1.11, 24.75) of frequent rehospitalisation, defined as ≥2 rehospitalisation within 30 days of index hospitalisation [8]. Many previous studies have investigated the effect of a compound variable representing 'cardiovascular comorbidities' on AECOPD incidence and severity; however, the heterogeneity of the various cardiovascular conditions included within such a compound variable may explain why these studies have found conflicting evidence [11,53,54].…”
Section: Hospitalisation and Rehospitalisationmentioning
confidence: 99%
“…Several studies have shown that COPD patients with HF experience more AECOPD and hospitalisations than those without HF [8][9][10]. Meanwhile, Jones et al did not find an association between cardiovascular comorbidity and AECOPD or mortality [11]; however, a composite cardiovascular exposure may not be indicative of the effects of individual cardiac conditions on COPD patients. Patel et al found that COPD patients with ischaemic heart disease, a precursor to HF, experienced longer exacerbations than COPD patients without ischaemic heart disease, but not more exacerbations [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a large‐scale study Jones et al investigated the correlation between CVD and exacerbation rates and mortality in COPD cohort. They concluded that the presence of CVD was not associated with increased risk of exacerbations or death, but with a higher risk of hospitalisation.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Mortality was higher in patients with systolic dysfunction (19.2%) compared with subjects who had preserved ejection fraction (4.8%). 96 In a large-scale study Jones et al 97 investigated the correlation between CVD and exacerbation rates and mortality in COPD cohort. They concluded that the presence of CVD was not associated with increased risk of exacerbations or death, but with a higher risk of hospitalisation.…”
Section: Cardiovascular Diseasementioning
confidence: 99%